[OA192] Kilovoltage rotational radiotheraphy with the marix/brixs source for partial breast irradiation. (August 2018) - Mettivier, Giovanni; Drebot, Illya; Bacci, Alberto; Petrillo, Vittoria; Rosetti, M.; Rossi, Andrea; Serafini, Luca; Calandrino, Riccardo; Cattaneo, Mauro; Fiorini, Claudio; Castriconi, Roberta; Sarno, Antonio; et al.
Abstract : Purpose: The development of compact sources of high brilliance, mono-chromatic, tunable X-rays with energy in the range 30–150 keV is a topical research field; applications in radiodiagnostics are foreseen. The aim of this work is to propose the use of a compact source based on X-ray Compton back-scattering (also known as Inverse Compton Source, ICS) developed within the MariX/BriXS project[1], for kilovoltage rotational radiotherapy dedicated to the breast. Methods: The proposed source is based on a modified Tigner scheme of push-and-pull twin Super-Conducting Energy Recovery Linacs, just wrapped on itself in order to halve the overall length of the machine. The ICS source was simulated by using the code CAIN and the output X-ray photon beam was obtained. The anticipated performances are a flux up to 10 13 photons/s within 5% bandwidth, coming in radiation pulses a few psec long at a repetition rate up to 100 MHz, fully tunable in the 20–150 keV energy range with full control of polarization and adjustable bandwidth in the range 0.5–10%. The simulated X-ray spectrum was used as an input of a previously validated Monte Carlo Geant4 code to calculate the dose distribution in a 50/50 breast phantom during a rotational radiotherapy scan. The pendant breast was modelled as a cylinder of 14 cm diameter and 9 cm height irradiated over 360 deg at 88 keV average energy and a 1-cm tumor was simulated at the isocenter. Results: The dose distribution obtained with the kilovoltage beam generated by the ICS source shows that it is possible to perform a partial breast irradiation with dose levels to the target and to the skin, compatible with clinical treatments using conventional linacs. Conclusions: We proposed the application of a Compton back-scattering X-ray source for kilovoltage rotational radiotherapy for breast cancer. The technique could be useful for partial breast irradiation with or without injection of a dose enhancement agent, for radiosurgery of small size breast tumors.